2023
DOI: 10.1038/s41467-023-39118-9
|View full text |Cite
|
Sign up to set email alerts
|

Pregnane X receptor agonist nomilin extends lifespan and healthspan in preclinical models through detoxification functions

Abstract: Citrus fruit has long been considered a healthy food, but its role and detailed mechanism in lifespan extension are not clear. Here, by using the nematode C. elegans, we identified that nomilin, a bitter-taste limoloid that is enriched in citrus, significantly extended the animals’ lifespan, healthspan, and toxin resistance. Further analyses indicate that this ageing inhibiting activity depended on the insulin-like pathway DAF-2/DAF-16 and nuclear hormone receptors NHR-8/DAF-12. Moreover, the human pregnane X … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…In previous research, no significant changes were found in EF or FS at 53 and 30 days [26] or EF at 5 weeks following DOX treatment [45]. Most studies on DOX toxicity focused on individual organs [10,14,27,46], and NAD + supplementation was suggested as an effective detoxification approach. Here, multi-organ and NAD + levels were detected in mice exposed to DOX.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In previous research, no significant changes were found in EF or FS at 53 and 30 days [26] or EF at 5 weeks following DOX treatment [45]. Most studies on DOX toxicity focused on individual organs [10,14,27,46], and NAD + supplementation was suggested as an effective detoxification approach. Here, multi-organ and NAD + levels were detected in mice exposed to DOX.…”
Section: Discussionmentioning
confidence: 93%
“…Excessive production of reactive oxygen species (ROS) during DOX metabolism also contributes to cardiomyopathy by causing biomolecular damage and activating pro-apoptotic pathways [7]. In addition to the heart, DOX accumulation [8], oxidative damage [9], inflammatory cell infiltration [10] and cytoplasmic vacuolization are also observed in the liver and kidneys of mice treated with DOX [11].…”
Section: Introductionmentioning
confidence: 99%
“…As known, dietary restriction prolongs lifespan in nematodes which are fed with E. coli OP50 (the standard experimental food for nematodes). While, previous studies showed that magnolol has antimicrobial effects 9,38 . To exclude the possibility that the lifespan-extending effect of magnolol was due to a decrease in food intake, we conducted the following experiments.…”
Section: Magnolol Extends Lifespan In C Elegansmentioning
confidence: 96%
“…Drosophila melanogaster mutant strain methuselah (mth) increased resistance to starvation, heat and paraquat stress 5 . At present, several drugs have been reported to enhance the resistance to stress to prolong the lifespan such as nomilin, tangeretin, apple and blueberry extract [6][7][8][9] . It demonstrates that enhancing the stress resistance of an organism may be a potential anti-aging therapy.Aging studies have been conducting using Caenorhabditis elegans (C. elegans) as a model for the highly conserved longevity genes and signaling pathways 4 .…”
mentioning
confidence: 99%
“…The expression of xenobiotic detoxification enzyme genes is regulated by the transcription of nuclear hormone receptors (NHRs) in mammals, including pregnane X receptor (PXR) and constitutive androstane receptor (CAR). Recently, we identified that targeting PXR extends lifespan and healthspan through the activation of detoxification functions in both C. elegans and mice (Fan et al, 2023). In C. elegans , NHR‐8 and DAF‐12 are the homologue of mammalian nuclear receptors, transcriptionally regulating the expression of detoxification enzymes and ATP‐binding cassette (ABC) transporters.…”
Section: Introductionmentioning
confidence: 99%